Mine Water and the Environment Journal of the International Mine Water Association (IMWA) - Kleinmann, Robert; Wolkersdorfer, Christian; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Mine Water and the Environment welcomes original contributions that address either technical questions or practical issues related to the evaluation, prediction, prevention, or control of water problems at mining operations or their impact on the environment. The journal and its audience is interdisciplinary. Manuscripts should convey new technical information and be of potential interest to researchers and/or practitioners in this field. Laboratory and field experiments, modelling efforts, studies of relevant field sites, technical evaluations of new technology, and engineering applications are all appropriate. Mine Water and the Environment was found in 1981 as International Journal of Mine Water.
Keywords: Water quality; Water pollution; Geology; Hydrogeology; Ecotoxicology; Pollution prevention; Geology; Water Quality/Water Pollution; Hydrogeology; Mineral Resources; Ecotoxicology; Industrial Pollution Prevention